Intentional Nitrite Ingestion: Clinical Presentation and Emergency Management in a Young Female Patient - Paolo Baldin; Francesca Cuoghi; Silvia Eichner; Ernani Savini; Giacomo Maroncelli; Benedetta Perna; Chiara Pesci; Michele Domenico Spampinato; Roberto De Giorgio; Matteo Guarino (Annals of Internal Medicine: Clinical Cases)
Sodium nitrite (NaNO₂) is an inorganic salt used in food preservation and industrial products, recently implicated in self-harm due to its easy online availability. We report a case of severe methemoglobinemia in a 20-year-old woman following sodium nitrite ingestion in a suicide attempt. The patient presented with cyanosis, hypotension, and elevated methemoglobin levels (64.1%). After poison control consultation, activated charcoal and methylene blue were administered, resulting in rapid clinical improvement and normalization of methemoglobinemia. This case emphasizes the importance of early recognition and treatment of sodium nitrite poisoning, highlighting the life-saving role of methylene blue.